Metal-catalyzed oxidation of human serum albumin does not alter the interactive binding to the two principal drug binding sites - Yamasaki, Keishi (Biochem Biophys Rep, 2018)
It is well known that various physiological factors such as pH, endogenous substances or post-translational modifications can affect the conformational state of human serum albumin (HSA). In a previous study, we reported that both pH- and long chain fatty acid-induced conformational changes can alter the interactive binding of ligands to the two principal binding sites of HSA, namely, site I and site II. In the present study, the effect of metal-catalyzed oxidation (MCO) caused by ascorbate/oxygen/trace metals on HSA structure and the interactive binding between dansyl-L-asparagine (DNSA; a site I ligand) and ibuprofen (a site II ligand) at pH 6.5 was investigated. MCO was accompanied by a time-dependent increase in carbonyl content in HSA, suggesting that the HSA was being oxidized. In addition, The MCO of HSA was accompanied by a change in net charge to a more negative charge and a decrease in thermal stability. SDS-PAGE patterns and α-helical contents of the oxidized HSAs were similar to those of native HSA, indicating that the HSA had not been extensively structurally modified by MCO. MCO also caused a selective decrease in ibuprofen binding. In spite of the changes in the HSA structure and ligand that bind to site II, no change in the interactive binding between DNSA and ibuprofen was observed. These data indicated that amino acid residues in site II are preferentially oxidized by MCO, whereas the spatial relationship between sites I and II (e.g. the distance between sites), the flexibility or space of each binding site are not altered. The present findings provide insights into the structural characteristics of oxidized HSA, and drug binding and drug-drug interactions on oxidized HSA.